Pollution liability insurance and corporate environmental compliance in China - Alecia Waite Cassidy; Fangjian Wu; Yiyuan Zhang (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This study examines the effect of a pollution liability insurance mandate on corporate environmental compliance in Shenzhen, China. We employ a triple differences design, comparing electroplating and circuit board manufacturing firms, mandated to purchase insurance, to industries and a neighboring city without the mandate. Results show a 0.48 reduction in annual environmental violations per firm (a 72% decrease). Only about half of firms comply. Within the Shenzhen electroplating and circuit board industry, we find that insured firms violate more than uninsured firms (an increase of about 0.09 annual violations). We find suggestive evidence that this increase is driven by moral hazard rather than adverse selection. Taken as a whole, our findings demonstrate that premium-based incentives effectively counteract market failures due to asymmetric information, increasing environmental compliance on net. – – Diese Studie untersucht die Auswirkungen einer Haftpflichtversicherung für Umweltverschmutzung auf die Einhaltung von Umweltvorschriften durch Unternehmen in Shenzhen, China. Wir verwenden ein Triple-Differenzen-Design und vergleichen Unternehmen der Galvanik- und Leiterplattenherstellung, die zum Abschluss einer Versicherung verpflichtet sind, mit Industrien und einer benachbarten Stadt ohne dieses Mandat. Die Ergebnisse zeigen eine Verringerung der jährlichen Umweltverstöße pro Unternehmen um 0,48 (ein Rückgang um 72 %). Nur etwa die Hälfte der Unternehmen erfüllt die Auflagen. In der Shenzhener Galvanik- und Leiterplattenindustrie stellen wir fest, dass versicherte Unternehmen mehr Verstöße begehen als nicht versicherte Unternehmen (ein Anstieg von etwa 0,09 jährlichen Verstößen). Wir finden Hinweise darauf, dass dieser Anstieg eher auf moralisches Risiko als auf negative Selektion zurückzuführen ist. Insgesamt zeigen unsere Ergebnisse, dass prämienbasierte Anreize Marktversagen aufgrund asymmetrischer Informationen wirksam entgegenwirken und die Einhaltung der Umweltvorschriften insgesamt verbessern.
Keywords: Q52; Q53; Q58; K32; G22; 330; Environmental compliance; liability insurance; moral hazard; adverse selection